2017
DOI: 10.1089/cap.2016.0153
|View full text |Cite
|
Sign up to set email alerts
|

Palatal Petechiae in the Absence of Group AStreptococcusin Pediatric Patients with Acute-Onset Neuropsychiatric Deterioration: A Cohort Study

Abstract: Despite the established relationship between palatal petechiae and GAS, no patient with palatal petechiae in our clinic tested positive for GAS and only 32% had evidence of recent GAS. Most did not have an identifiable cause for the palatal lesions. This finding suggests the potential for alternative causes of palatal petechiae or undetectable GAS in our patient population. The high prevalence of palatal petechiae without GAS infection suggests that the pathogenesis of PANS is multifactorial and may involve di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…That such mechanisms may indeed be critical in PANS is suggested by the efficacy of anti-inflammatory therapies, most commonly ibuprofen and steroids, in attenuating PANS symptoms among patients in this study. Although treatment with other anti-inflammatories, such as naproxen and celecoxib, appears to be rare in the PANS population, the positive reports collected in this survey suggest that this anti-inflammatory treatment strategy may deserve further study (Mahony et al 2017 ).…”
Section: Discussionmentioning
confidence: 90%
“…That such mechanisms may indeed be critical in PANS is suggested by the efficacy of anti-inflammatory therapies, most commonly ibuprofen and steroids, in attenuating PANS symptoms among patients in this study. Although treatment with other anti-inflammatories, such as naproxen and celecoxib, appears to be rare in the PANS population, the positive reports collected in this survey suggest that this anti-inflammatory treatment strategy may deserve further study (Mahony et al 2017 ).…”
Section: Discussionmentioning
confidence: 90%
“…Slightly fewer than half of the patients, 46%, exhibited ear, nose, and throat (ENT) infection signs at onset/first assessment. Nine percent had palatal petechiae as a suspected sign of streptococcal infection (Mahony et al 2017b). Skin abnormalities, including dermatographia, livedo, rashes, and/or eczema, were present in 61% of patients.…”
Section: Resultsmentioning
confidence: 99%
“…Other diseases of known etiology, but with a similar clinical picture, such as Sydenham's chorea, systemic lupus erythematosus, or other inflammatory encephalitides, such as anti-NMDA receptor encephalitis, need to be excluded (Dalmau et al 2008; Dale and Brilot 2012; Hacohen et al 2013; Ramanathan 2014). While the etiology is unknown, infectious agents such as group A streptococci (GAS), mycoplasma, and Epstein–Barr virus as well as AD and inflammatory disorders have been described as contributing to the pathogenic mechanisms and potential triggers for the constellation of symptoms that constitute PANS (Kurlan et al 2008; Leckman et al 2011; Brimberg et al 2012; Cutforth et al 2016; Mahony et al 2017a, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, it is still hard to reach a homogeneous, validated diagnostic pathway because of the difference between the conceptual frames and the diagnostic tools used by diverse groups. A recent review 105 suggested that, taken individually, no single biomarker is specific for the diagnosis of PANS.…”
Section: Clinical Managementmentioning
confidence: 99%